1999
DOI: 10.1111/j.1574-6968.1999.tb08830.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and sequences of inducible and constitutive macrolide resistance genes inStaphylococcus aureusthat correspond to an ABC transporter

Abstract: A restriction map was made and the DNA sequence was determined for a plasmid, pMC38, derived from the inducible macrolide resistance plasmid pEP2104, that showed constitutive resistance to PMS antibiotics (partial macrolide and streptogramin B antibiotics). A 5. 04 kb SalI-PstI fragment (fragment C) of pMC38, which encoded PMS resistance, was cloned into a shuttle vector, pRIT5, to yield pMR504. The transformant Staphylococcus aureus 4220 (pMR504) exhibited constitutive PMS resistance. Fragment C was subcloned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…20,32 . In the present study, the msr (A) gene was detected in isolates having MIC I of 8 mg/L, supporting the loss of activity of this gene when cloned in E. coli 33 . The other ATP binding transporter studied, Msr(D), it was detected independently of the presence of Mef(A).…”
Section: Discussionsupporting
confidence: 83%
“…20,32 . In the present study, the msr (A) gene was detected in isolates having MIC I of 8 mg/L, supporting the loss of activity of this gene when cloned in E. coli 33 . The other ATP binding transporter studied, Msr(D), it was detected independently of the presence of Mef(A).…”
Section: Discussionsupporting
confidence: 83%
“…In contrast to the use of radiolabeled antibiotics and measurement by liquid scintillation counter [8,16,17], we lysed the cells, isolated the target compounds, and determined their concentrations by LC-MS/MS, the “gold standard” for the identification and quantification of small molecules [19,20]. During the sample preparation procedure, we focused on the rapid separation of bacterial cells from culture medium and minimization of cell membrane disruption.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Sharkey et al provided the first direct evidence that Vga and Lsa-type proteins confer resistance by acting directly on the ribosome [15]. However, previous studies showed that Staphylococcus aureus and Staphylococcus haemolyticus carrying msr or vga exhibited decreased intracellular accumulation of the corresponding target antibiotics [8,16,17], although this may also result from ribosomal protection [8]. Until now, little has been known regarding the resistance mechanism of optrA .…”
Section: Introductionmentioning
confidence: 99%
“…MLS resistance genes (ermA, ermB, ermC, msrA/B, lnuA, lnuB, and lsaA) were identified by multiple PCR methods on 60 isolates from the total number of tested enterococcal strains for which the MLS resistance phenotype was determined using primers, whose sequences have been previously published (Table 1) [12,[18][19][20].…”
Section: Isolation Of Dna and Pcr Primersmentioning
confidence: 99%